Página web: Escenarios futbolísticos que sirvieron de propaganda política durante las copas mundiales Italia 1934 y Francia 1938. (2022)
The present research work corresponds to the modality of teaching material, in this proposal you will find a succinct approach to various investigations related to didactic material such as innovative methodologies to teach Social Sciences